Mathematical simulation of deciduous tree ignition by cloud-to-ground lightning discharge using large vessels approximation; JP Journal of Heat and Mass Transfer; Vol. 14, iss. 4 - Baranovskiy N. V. Nikolay Viktorovich (2017, 2017)
Title screen